Assessments of health workers on the implementation of the safety system in the use of medications - Restrepo Vásquez, Aleyda; Escobar Montoya, Julia Inés (Universidad y Salud, 2017)
Introduction: Errors in medication is one of the most frequent adverse events in most of the countries in Latin America, which has led to promote a system for its identification and reduction in health institutions. Objective: To determine the assessments of health personnel on the degree of implementation of the system of patient safety in the use of medicines. Materials and methods: A quantitative descriptive study with a population of 73 health workers was conducted. A survey was designed based on two instruments: the self-assessment questionnaire for the security of the system for the use of medicines in hospitals and the questionnaire on patient safety: Spanish version of the Hospital of the Ministry of Health and Consumption, and they were contrasted with the guidelines of the patient security policy for Colombia. The answers were measured by a scale with four categories: strongly agree, agree, disagree and do not know. Results: The average percentage of people who indicated a total compliance in the implementation of the policy in the standardization was of 65.1%, storage and distribution of medicines in its prescription 61.7%, and 65.5% in its administration and registration. Conclusions: It was evidenced that approximately half the respondents appreciated lack of compliance in the implementation of the system of patient safety that frames the processes of drug use in all its stages. The foregoing reveals that while there is a security system in the patients' medication in the institutions studied in theory, there is a need to strengthen the management actions aimed at ensuring its effective implementation with all actors involved, being the permanent monitoring of the processes a fundamental pillar.